Uporaba metode fotogrametričnih časovnih vrst za spremljanje sortiranih strukturnih tal v jamskem okolju - Zore, Marko (Geodetski vestnik, 2025)
The paper presents a method for observing particles on sorted patterned ground in a karst cave. Due to repeated freeze-thaw cycles, fine-grained sediment and gravel can be sorted and arranged in circular patterns. These landforms are characteristic of cold, vegetation-free environments, but they can also be found in karst caves in Slovenia. Sorted patterned ground is often associated with the process of cryoturbation, which is still poorly understood. Observing particle movements on sorted patterned ground can provide unique insights into the cryoturbation process. The purpose of this paper is to analyse the suitability of photogrammetrically derived dense point clouds, based on Structure from Motion method application, for monitoring particle movements on sorted patterned ground in the Barka cave on the Snežnik Plateau, Slovenia. We used this method to create 3D dense point clouds from four convergent photographs of the sorted circles for each day and performed a time series analysis for the period from mid-December 2022 to mid-June 2023. We successfully detected vertical sediment movements of several centimetres during freeze-thaw cycles within an accuracy of 2.3 mm.
Keywords: Barka cave; cryoturbation; fotogrametrija; jama Barka; krioturbacija; morphological changes; photogrammetry; reliefne spremembe; Slovenia; Slovenija